HUBUNGAN ASUPAN ASAM LEMAK OMEGA-3 DAN OMEGA-6 DENGAN TEKANAN DARAH WANITA USIA 30 – 50 TAHUN - Sari, Mega Lucyta; Probosari, Enny; Wijayanti, Hartanti Sandi (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2017)
Background: Hypertension is one of the major risk factors for cardiovascular disease. Decreased intake of omega-3 and increased intake of omega-6 can increase the risk of hypertension. Hypertension cases in Indonesia are highest in women especially aged 30 - 50 years. This study aimed to determine correlation of omega-3 and omega-6 intake with blood pressure in women aged 30-50 years.Method : This was an observational research with cross-sectional study design. Fifty four subjects were selecting using consecutive sampling. Intakes were assessed by food recall 2x24 hours. Blood pressure levels were measured by Sphygmomanometer. Data were analyzed by Chi Square and Fisher Exact.Result : Systolic and diastolic blood pressure mean were 115.92 ± 14.5 mmHg and 75 ± 7.45 mmHg, while omega-3 and omega-6 mean were of 3. 1.03 ± 0.52 g and 14.17 ± 5 , 8 g. More than one third of the subjects (37.9%) with pre-hypertension/hypertension had omega-3 intake less than 1.1 g and 52.7% of them had omega-6 intake less than 12 g.There was correlation of omega-6 intake with systolic blood pressure (p <0.05) but there were no correlation between omega-3 intake with systolic blood pressure, omega-3 and omega-6 intake with diastolic blood pressure (p >0,05). Conclusion: There was correlation of omega-6 intake with systolic blood pressure, there were no correlation between omega-3 intake with systolic blood pressure, omega-3 and omega-6 intake with diastolic blood pressure